Matched - Condie, Allyson Braithwaite (London : Penguin Books, 2010)
Cassia has always had complete trust in the Society to make decisions for her, but when she is being paired with her ideal mate, a second face flashes on the screen, and Cassia begins to doubt the Society's infallibility as she tries to decide which man she truly loves.
Booklist
Kirkus Starred
Pub Weekly
Booklist, September 2010
Bulletin (Center for Children's books), November 2010
Kirkus Starred, October 2010
Keywords: Mate selection -- Juvenile fiction; Self-realization -- Juvenile fiction; Triangles (Interpersonal relations) -- Juvenile fiction; Fantasy; Mate selection -- Fiction; Self-realization -- Fiction; Triangles (Interpersonal relations) -- Fiction; Interpersonal relations -- Fiction; Self-realization -- Fiction; Fantastic fiction; Fantastic fiction